Efficacy of sputum induction from lower respiratory tract in children - Madeleine Ramdhani Jasin; Darmawan Budi Setyanto; Sri Rezeki Hadinegoro; Lisnawati Lisnawati; Pramita Gayatri; Nia Kurniati (Indonesian Pediatric Society, 2015)
Background Although sputum is a good specimen for variousexaminations, such as cytology and microbiological culture,sputum induction (SI) is not a routine procedure in children.Objective To identify the efficacy of SI to obtain specimen fromlower respiratory tract in children, identify side effects of SI, andthe results of microbiological examination.Methods A cross sectional study was performed in children (aged1 month to 18 years) who underwent SI. Sputum induction wasperformed by inhalation with hypertonic solution, consisted ofsalbutamol for 15 minutes continued with NaCl 3% solutionfor another 15 minutes. Sputum specimens were examined fornumber of alveolar macrophage cell, surfactant protein A (SP-A)concentration, also acid-fast bacili smear, and M. tuberculosisculture, or aerobic microbial culture.Results Forty subjects with lower respiratory tract infectionparticipated in this study, and SI was succesfully performed inall subjects. Youngest subject was 2 month old, the eldest was 16year 7 month old. Median duration of SI was 45 minutes, andmajority of volume was 3 or 4 mL. Side effects were nosebleeds(40%) and vomiting (2.5%). Macrophage alveolar more than 5cells in one specimen was found in 97.5% subjects. Surfactantprotein A examination was performed in 30 specimens, and SP-Awas detected in all specimens (median concentration 264.528 pg/mL). Culture for M. tuberculosis was positive in 1 of 27 subjects,while acid fast bacili smear was negative in all examined subjects.Aerobic microbial culture was positive in 5 of 13 subjects.Conclusions Sputum induction has good efficacy in obtaininglower respiratory tract specimen and it is safe to perform inchildren. Specimen from sputum induction yields good positiveresult for aerobic microbial cultures.